Heat transfer under conditions of operation of a gas infrared emitter and an air exchange system; Journal of Physics: Conference Series; Vol. 2057 : Thermophysics and Physical Hydrodynamics and the school for young scientists "Thermal physics and physical hydrodynamics: modern challenges" (TPH 2021) - Borisov B. V. Boris Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna; Vyatkin A. V. Aleksandr Vitaljevich (2021, 2021)
Title screen